Evaluasi System Usability Scale Pada Sistem Presensi Pengunjung Resource Center - Rumini Rumini; Norhikmah Norhikmah (STMIK Budi Darma, 2022)
Resource center (RC) or can be called also in this case is a library. The library is a place to study or to access information. The RC system of Amikom Yogyakarta University has attendance services for visitors from the user side, namely internal students and external visitors and stores visitor data to find out how many people visit the library, both internal and external visitors. Usability problems that usually appear in system features for users, indicate the need for usability testing. Usability testing uses the SUS (System Usability Scale) method in order to find problems with the visitor attendance system by referring to usability principles, which can involve users. This research was conducted in 3 main stages, namely compiling a questionnaire in accordance with the provisions of the SUS method, processing the results of the respondents' answers from those distributed to visitors by the SUS method rules to obtaining test results in the form of SUS scores. Based on the results of the evaluation carried out, the average SUS score from the study was 55.56, which means it has a D rating (less) which indicates that the presence system visitor feature cannot be accepted by users from the usability aspect, it is still minimal in use, because it only stores visitor data, the recommendations given from the results of this evaluation in order to increase usability for visitor features are such as visitor entry hours, exit hours, input facilities in the form of input related to collections of books, journals, magazines, e-books, facilities inside, room atmosphere, and others, because things like this affect the optimal library services for visitors.